Analysis of the Welcome Monument Dispute Case by Grand Indonesia Mall in terms of Law Number 28 of 2014 concerning Copyright - Blessyah, Glorya Heavennina; Setiawan, Florencia Lavina; Priscilla, Nathalie; Putra, Moody Rizqy Syailendra (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Copyright is regulated in Law Number 28 of 2014. In accordance with statutory provisions. This journal discusses the dispute case between the heirs of the creator of the Selamat Datang Monument and PT Grand Indonesia. In 1962, the Welcome Monument which was located at the Hotel Indonesia Roundabout had the meaning of welcoming the participants when Jakarta was the host of the Asian Games. But after the end of the Asian Games, the Selamat Datang Monument became a welcoming icon for guests who came to the center of the capital city, namely Jakarta. After that, PT Grand Indonesia was deemed to have violated copyright because it used the Tugu Selamat Datang logo without permission.